Carol W Brown with bust of John Steinbeck - Unknown:::Creator::::::::::::
Carol W. Brown sculpted the second bust of Steinbeck after the first was stolen in 1991. Mrs. Brown had done the original in 1972. Mrs. Brown was a former sister-in-law and classmate of Elaine Steinbeck